Evaluating maternal toxicity induced by aqueous extract of Bambusa vulgaris shoot through biochemical, hematological, and histopathological assessment in pregnant Wistar rats - Biswajeet Acharya; Amulyaratna Behera; Prafulla Kumar Sahu; Bimalendu Chowdhury; Suchismeeta Behera (Advances in Bamboo Science, 2024)
Exposure to teratogenic agents during pregnancy can lead to fetal abnormalities. Establishing histological, hematological, and biochemical parameters is pivotal to enhancing the evaluation of the effect of any substance on embryo-fetal development. The present study investigated the maternal toxicity of aqueous extract of Bambusa vulgaris Schrad. ex J.C. Wendl shoots in pregnant Wistar rats. The pregnant rats were then allocated into four groups (n=6): a control group (without treatment) and three test groups (treated with the extract 250, 500, and 1000 mg/Kg, respectively). The treatment was initiated on gestational day (GD) 6 and continued until the 15th day. On GD 20, all the rats were anesthetized and subjected to laparotomy. Blood samples were collected from the pregnant rats for hematological and biochemical analyses, while various organs were isolated for histopathological studies. The study demonstrates dose-dependent toxicity of the extract, with significant variations (P<0.001) observed in ALP and AST levels at the 1000 mg/kg dose, suggesting hepatic impairment in maternal subjects. Moreover, significant variations in total leukocyte and lymphocyte counts suggested pronounced inflammation or multi-organ dysfunction at this dose. Histopathological examination also revealed various indicators of multi-organ failure, including transmural mixed inflammation in the gall bladder, disruption of cardiac myofibre arrangement, tubular cell damage in the kidneys, cellular alterations in the liver, shrinking of pancreatic Langerhans islets, and lymphoid depletion in the spleen at 1000 mg/kg dose. These findings underscore the potential maternal toxicity associated with Bambusa vulgaris shoots, highlighting its potential risk for consumption during pregnancy and emphasizing the need for further research and caution regarding its use during this critical period.